Aimé Bonpland's drawings of Itá Pucú, 1834, and the history of early geological representations in Argentina - Ottone, Eduardo Guillermo (2004)
The early geological representations in Argentina dated from the middle of the nineteenth century when Alcide d'Orbigny, Charles Darwin, Bartholomew James Sulivan, Franz Foetterle, Auguste Bravard, Jakob Christen Heusser and Georges Claraz, and Victor Martin de Moussy accompanied their scientific observations with geological maps, stratigraphic sections or sketches of rocky outcrops. Aimé Bonpland (1773-1858), a French naturalist mainly known by his travels with Alexander von Humboldt and by his contributions on tropical botany, settled in southern South America in 1817, and displayed a relevant activity as botanist, zoologist, paleontologist, and geologist. In this last field, Bonpland prepared in 1834 a series of drafts and drawings about the geology of the Itá Pucú that constitute one of the first geological representations to the country and it is the first document providing a detailed description and a schematic graphical representation of a sedimentary outcrop.